Resin composition for bonded magnet and bonded magnet molded article molded using same

By using a resin composition for bonded magnets with a high content of magnetic powder and a PA10 skeleton resin, the shortcomings of bonded magnets in the prior art in terms of heat resistance, mechanical strength and water absorption are solved, and a high-performance, low-water absorption bonded magnet molded body is realized.

CN119731752APending Publication Date: 2025-03-28TODA KOGYO CORP
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202380059565.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-09-14
Filing Date
2023-08-28
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The conventional resin composition for bonded magnets has concerns regarding heat resistance, dimensional accuracy and mechanical strength, especially the materials of polyamide 6, polyamide 12 or PPS resin have a reduced strength at high temperatures and a high water absorption rate.

Method used

A resin composition for bonded magnets containing at least 70% by weight of magnetic powder and 5 to 30% by weight of resin having a PA10 skeleton as the binder resin, and an inorganic reinforcement material may optionally be added therein.

Benefits of technology

The bonded magnet molded body without reducing magnetic characteristics and has high heat resistance, bending strength and IZOD impact strength, and is also low in water absorption, making it suitable for high-performance bonded magnets.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005270380640000091
    Figure BDA0005270380640000091
  • Figure BDA0005270380640000101
    Figure BDA0005270380640000101
  • Figure BDA0005270380640000111
    Figure BDA0005270380640000111
Patent Text Reader

Abstract

According to one embodiment of the present invention, it is possible to provide: a resin composition for bonded magnets, which has excellent physical properties such as heat resistance, bending strength, and IZOD impact strength without deteriorating magnetic properties, and which has a low water absorption rate; and a bonded magnet molded article molded using the resin composition. The resin composition for a bonded magnet contains at least a magnetic powder and a binder resin, and contains 70 wt% or more of the magnetic powder and 5-30 wt% of a resin having a PA10 skeleton as the binder resin.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a resin composition for bonded magnets and a bonded magnet molded body molded using the resin composition. Background Art

[0002] It is well known that bonded magnets have advantages over sintered magnets, such as being lightweight, having good dimensional accuracy, and being easy to mass-produce even complex-shaped products. Therefore, bonded magnets are widely used in various applications such as toys, office equipment, audio equipment, and motors.

[0003] As magnetic powders for bonded magnets, rare earth magnet powders represented by Nd-Fe-B and ferrite particle powders are known. Rare earth magnet powders have high magnetic properties, but are also expensive and have limited uses. On the other hand, ferrite particle powders are inferior to rare earth magnet powders in magnetic properties, but are inexpensive and chemically stable. Therefore, ferrite particle powders can be used in a wide range of applications.

[0004] Generally speaking, bonded magnets are manufactured by kneading rubber or plastic materials with magnetic powder and then molding them in a magnetic field or using mechanical methods.

[0005] In recent years, with the advancement of high functionality including improved productivity of various materials and equipment and improved reliability during use, there is a demand for higher performance including improved productivity, improved mechanical strength, and improved magnetic properties of bonded magnets used.

[0006] For example, bonded magnets are used as rotors and sensors in vehicles. In order to prolong the life of the device and use it at high speed, high heat resistance and high mechanical strength are strongly required. Therefore, bonded magnets using polyamide resin or PPS resin as binder resin are used. Polyamide resin and PPS resin are considered to have high heat resistance and little reduction in mechanical properties at high temperatures.

[0007] For example, Patent Document 1 proposes to prepare a bonded magnet compound having high heat resistance, excellent mechanical strength and magnetic properties by mixing polyamide 6 or polyamide 12 with non-magnetic powder in a specified ratio. Patent Document 2 proposes to prepare a bonded magnet compound having high heat resistance, excellent mechanical strength and magnetic properties by adding modified polyolefins and glass fibers to PPS resin.

[0008] Furthermore, Patent Document 3 proposes a bonded magnet resin composition containing a phosphorus-based antioxidant in order to obtain a bonded magnet having little strength reduction even when exposed to a high-temperature environment.

[0009] Prior art literature

[0010] Patent Literature

[0011] Patent Document 1: Japanese Patent Application Publication No. 2005-72240

[0012] Patent Document 2: Japanese Patent Application Laid-Open No. 4-44304

[0013] Patent Document 3: Japanese Patent Application Publication No. 2015-76572 Summary of the invention

[0014] However, for bonded magnets using polyamide 6, polyamide 12 or PPS resin, there are concerns about heat resistance, dimensional accuracy and strength due to the influence of the melting point, water absorption and strength of the resin. Therefore, there is a strong demand for materials with high melting point, low water absorption and high strength.

[0015] Therefore, a technical problem of the present disclosure is to obtain a resin composition for bonded magnets that does not reduce magnetic properties, has excellent physical properties such as heat resistance, bending strength and IZOD impact strength, and has low water absorption, as well as a molded body molded using the resin composition.

[0016] The above technical problems can be achieved by the following aspects of the present disclosure.

[0017] That is, the bonded magnet resin composition according to one embodiment of the present disclosure includes at least magnetic powder and a binder resin, contains 70 wt % or more of the magnetic powder, and contains 5 to 30 wt % of a resin having a PA10 skeleton as the binder resin (first embodiment).

[0018] In the bonded magnet resin composition of the first embodiment, the melting point of the resin having the PA10 skeleton may be 200° C. or higher (second embodiment).

[0019] The bonded magnet resin composition of the first or second embodiment may contain 10 wt % or less of an inorganic reinforcing material (third embodiment).

[0020] Furthermore, a bonded magnet molded body according to one embodiment of the present disclosure is a bonded magnet molded body molded using any one of the bonded magnet resin compositions of the first to third embodiments (fourth embodiment).

[0021] A molded body molded using the bonded magnet resin composition according to one embodiment of the present disclosure has high physical properties such as bending strength and IZOD impact strength without reducing Br (residual magnetic flux density) and has low water absorption. Therefore, the molded body is suitable as a bonded magnet. DETAILED DESCRIPTION

[0022] Hereinafter, embodiments of the present disclosure will be described in detail.

[0023] The bonded magnet resin composition of the present embodiment contains at least magnetic powder and a binder resin.

[0024] The magnetic powder of the present embodiment is not particularly limited. As the magnetic powder, magnetic powder generally used for bonded magnets, such as ferrite particle powder or rare earth magnetic powder, can be used.

[0025] The ferrite particle powder is preferably a magnetoplumbite type ferrite particle powder. The magnetoplumbite type ferrite particle powder is represented by the formula AO·nFe2O3 (wherein A is Ba, Sr or Ba-Sr, and n=5.0 to 6.5). Examples of ferrite particle powder represented by this formula include barium ferrite particle powder, strontium ferrite particle powder, and barium-strontium ferrite particle powder. In these ferrite particle powders, as constituent elements, 0.1 to 7.0 mol% of one or more elements selected from Ti, Mn, Al, La, Zn, Bi and Co may also be contained.

[0026] The average particle size of the ferrite particle powder is preferably 1.0 to 5.0 μm, more preferably 1.0 to 2.0 μm. The BET specific surface area of ​​the ferrite particle powder is preferably 1 to 10 m 2 / g, more preferably 1 to 5 m 2 / g. The coercive force iHc of the ferrite particle powder is preferably 119 to 557 kA / m (1500 to 7000 Oe), and more preferably 119 to 398 kA / m (1500 to 5000 Oe). The remanence of the ferrite particle powder is preferably 100 to 300 mT (1000 to 3000 G), and more preferably 100 to 200 mT (1000 to 2000 G).

[0027] Rare earth magnetic powder is an intermetallic compound containing at least one rare earth element and at least one transition metal in its constituent elements. For example, rare earth magnetic powders include rare earth cobalt-based, rare earth-iron-boron-based, and rare earth-iron-nitrogen-based magnetic powders. In particular, when rare earth-iron-boron-based magnetic powders and rare earth-iron-nitrogen-based magnetic powders are used, a bonded magnet having excellent magnetic properties can be obtained.

[0028] The average particle size of the rare earth magnetic powder is preferably 1 to 120 μm, more preferably 1 to 80 μm. The BET specific surface area of ​​the rare earth magnetic powder is preferably 0.5 to 5 m 2 / g, more preferably 0.5 to 3 m 2 / g. The coercive force iHc of the rare earth magnetic powder is preferably 239 to 1591 kA / m (3.0 to 20 kOe), and more preferably 318 to 1114 kA / m (4.0 to 15 kOe). The remanence of the rare earth magnetic powder is preferably 0.3 to 1.8 mT (3.0 to 18 kG), and more preferably 0.5 to 1.3 mT (5.0 to 13 kG).

[0029] It should be noted that the Nd-Fe-B magnetic powder can also be used directly for kneading. However, when the Nd-Fe-B magnetic powder is a flaky powder, in order to obtain higher fluidity and magnetic properties, it is preferred to use a jet mill, an atomizer or a ball mill to crush the Nd-Fe-B magnetic powder to an average particle size of 100 μm or less.

[0030] Examples of soft ferrite particle powder include Mn-Zn ferrite, Ni-Zn ferrite, Ni-Zn-Cu ferrite, Mn-Mg ferrite, carbonyl iron powder, iron dust, etc. Soft ferrite having a composition that changes depending on the frequency of the electromagnetic wave used may also be used.

[0031] The average particle size of the soft ferrite powder is preferably 1 to 150 μm, more preferably 1 to 50 μm.

[0032] These magnetic powders are preferably subjected to various surface treatments in order to suppress deterioration of magnetic properties due to oxidation, improve compatibility with resins, and improve the strength of molded bodies.

[0033] As materials that can be used for surface treatment, there can be mentioned silane coupling agents, titanium coupling agents, aluminum coupling agents, siloxane polymers, organic phosphoric acid surface treatment agents, inorganic phosphoric acid surface treatment agents, etc. In particular, by pre-treating the surface of the magnetic powder with a silane coupling agent, the strength of the molded body can be further improved.

[0034] The content of magnetic powder in the resin composition for bonded magnets of this embodiment is 70% by weight or more. When the content of magnetic powder is less than 70% by weight, it is difficult to obtain the required magnetic properties. Since the content of magnetic powder exceeding 95% by weight will reduce the mechanical strength of the resulting bonded magnet and reduce the moldability such as fluidity and circulability, it is not preferred. The content of magnetic powder is more preferably 75 to 93% by weight, and further preferably 77 to 91% by weight.

[0035] The binder resin in the present embodiment contains a resin having a PA10 skeleton as a main component. The resin having a PA10 skeleton refers to a bio-based polyamide synthesized mainly using sebacic acid derived from castor oil, such as PA410, PA610, and PA1010.

[0036] The resin composition for bonded magnets of the present embodiment contains 5 to 30 weight % of a resin having a PA10 skeleton as a binder resin. When the content of the resin having a PA10 skeleton is less than 5 weight %, sufficient fluidity of the resin composition for bonded magnets cannot be obtained, and the mechanical strength of the bonded magnet is reduced. Therefore, it is difficult to obtain a good molded body. When the content of the resin having a PA10 skeleton exceeds 30 weight %, the magnetic properties are reduced. The content of the resin having a PA10 skeleton is preferably 7 to 25 weight %, and more preferably 10 to 23 weight %.

[0037] The resin having a PA10 skeleton used in the bonded magnet resin composition of the present embodiment has low water absorption, and therefore, a molded body obtained by molding the resin has high dimensional stability.

[0038] The resin having a PA10 skeleton used in the bonded magnet resin composition of the present embodiment has a long carbon chain and a relatively high melting point. For example, the melting point of PA410 is 250°C, the melting point of PA610 is 225°C, and the melting point of PA1010 is 205°C. Since the melting point of the resin is above 200°C, the heat deformation temperature of the molded body obtained by using the bonded magnet resin composition is increased, and thus it is preferred.

[0039] The resin with a PA10 skeleton used in the resin composition for bonded magnets of the present embodiment is not particularly limited. However, the average molecular weight of the resin is preferably 10,000 to 100,000. In the case of using a low molecular weight resin with a PA10 skeleton, the moldability of the resin composition for bonded magnets is excellent due to the low melt viscosity of the resin, but on the other hand, the physical properties such as strength of the obtained molded body are poor. On the other hand, in the case of using a high molecular weight resin with a PA10 skeleton, for the resin composition for bonded magnets, the strength of the obtained molded body is excellent, but due to the high viscosity of the resin, if the filling amount of the magnetic powder is increased, the moldability deteriorates.

[0040] The bonded magnet resin composition of the present embodiment may contain, as a binder resin, a polyamide resin and / or various elastomers as needed, in addition to the resin having a PA10 skeleton, within a range that does not impair the properties of the bonded magnet resin composition of the present embodiment.

[0041] As inorganic reinforcing materials, glass fibers and the like can be used. In the resin composition for bonded magnets of the present embodiment, inorganic reinforcing materials may be contained within the range that does not damage its characteristics. The content of inorganic reinforcing materials is preferably less than 10% by weight. The content of inorganic reinforcing materials is more preferably 1 to 8% by weight, and further preferably 2.1 to 7% by weight.

[0042] In the resin composition for bonded magnets of the present embodiment, the residual magnetic flux density Br when using the above-mentioned ferrite particle powder as the magnetic powder is preferably 170mT (1700G) or more, and more preferably 175mT (1750G) or more. The coercive force iHc of the resin composition for bonded magnets is preferably 119 to 279kA / m (1500 to 3500Oe), and more preferably 127 to 259kA / m (1600 to 3250Oe). The maximum energy product (BH)max of the resin composition for bonded magnets is preferably 5.5kJ / m 3 (0.70MGOe) or more, more preferably 10.7 kJ / m 3 The values ​​of the residual magnetic flux density Br, the coercive force iHc and the maximum energy product (BH)max are values ​​measured for the molded body by the magnetic measurement method described later.

[0043] In the resin composition for bonded magnets of the present embodiment, the residual magnetic flux density Br when the above-mentioned rare earth magnetic powder is used as the magnetic powder is preferably 300mT (3000G) or more, and more preferably 350mT (3500G) or more. The coercive force iHc of the resin composition for bonded magnets is preferably 636 to 955kA / m (8000 to 12000Oe), and more preferably 676 to 915kA / m (8500 to 11500Oe). The maximum energy product (BH)max of the resin composition for bonded magnets is preferably 15.9kJ / m 3 (2.00MGOe) or more, more preferably 19.9 kJ / m 3 The values ​​of the residual magnetic flux density Br, the coercive force iHc and the maximum energy product (BH)max are values ​​measured for the molded body by the magnetic measurement method described later.

[0044] The flexural strength of the molded body formed using the bonded magnet resin composition of this embodiment is preferably 110 MPa or more. If the flexural strength is less than 110 MPa, cracks (fissures) are likely to occur in the molded body due to low mechanical strength of the molded body.

[0045] The IZOD impact strength of a molded body molded using the bonded magnet resin composition of this embodiment is preferably 10 kJ / m 2 When the IZOD impact strength is less than 10kJ / m 2 When the molded body is molded, cracks (cracks) are likely to occur due to the low mechanical strength of the molded body.

[0046] The deflection temperature under load of the molded body molded using the bonded magnet resin composition of the present embodiment is preferably 140° C. or higher. When the deflection temperature under load is lower than 140° C., the molded body may be deformed in a high temperature environment.

[0047] The water absorption of the molded body formed using the bonded magnet resin composition of this embodiment is preferably 1.0 wt % or less. If the water absorption exceeds 1.0 wt %, the molded body swells, and dimensional changes and / or cracks (breaks) may occur in the molded body.

[0048] Next, a method for producing the bonded magnet resin composition according to the present embodiment will be described.

[0049] The resin composition for bonded magnets of the present embodiment can be obtained by a known method for manufacturing a resin composition for bonded magnets. The resin composition for bonded magnets can be obtained by, for example, uniformly mixing magnetic powder and a resin component having a PA10 skeleton, then melt-kneading the mixture using a kneading extruder, and crushing or cutting the kneaded material into granules or particles.

[0050] The bonded magnet resin composition of the present embodiment may arbitrarily contain a plastic molding lubricant, various stabilizers, and the like in order to improve moldability, improve heat resistance, and obtain anti-oxidative degradation and rust prevention effects.

[0051] As the lubricant used, for example, there can be mentioned substances of carboxyl saturated / unsaturated fatty acid system such as propionic acid, stearic acid, linoleic acid, oleic acid, malonic acid, glutaric acid, adipic acid, maleic acid and fumaric acid, and compounds of these substances. As compounds of these substances, for example, there can be mentioned metal soaps such as calcium stearate, magnesium stearate and lithium stearate, fatty acid amides such as hydroxybisstearamide, ethylenebislauric acid amide and ethylenebisoleic acid amide, waxes such as paraffin, polysiloxanes such as dimethylpolysiloxane and silicone oil, and fluorine compounds such as fluorine-containing oil.

[0052] As a stabilizer, an antioxidant is preferably added to prevent degradation due to heat. As an antioxidant, for example, a metal deactivator and a stabilizer can be used. As an example of a metal deactivator, N, N'-bis[3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionohydrazide can be cited. As an example of a stabilizer, hindered amine stabilizers, pentaerythritol-tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate] and other hindered / low hindered phenol stabilizers, phosphite stabilizers, and thioether stabilizers can be cited. It is particularly effective to use a hindered / low hindered phenol stabilizer and a phosphite stabilizer or a metal deactivator at the same time.

[0053] The antioxidant is contained in an amount of preferably 0.1 to 1.0 wt %, more preferably 0.2 to 0.8 wt %, based on the total amount of the resin composition.

[0054] Furthermore, a known mold release agent such as zinc stearate or calcium stearate may be added to the resin as necessary.

[0055] There is no particular limitation on the molding method used to obtain a molded body molded using the resin composition for bonded magnets of the present embodiment. As the molding method, known methods can be used alone or in combination according to the material properties, molding purpose and use of the resin composition for bonded magnets. As known methods, for example, a conveying method, an injection method, an extrusion method, an inflation method, a rolling method, a T-die method, a blowing method, a vacuum method, a lamination method, a spray method, a foaming method, a mold-to-mold method and an SMC method can be cited. In particular, in a resin composition for bonded magnets using a thermoplastic resin, an injection method or an extrusion method is preferably used. These methods are methods applied to many industrial components. According to these methods, continuous and high-speed mass production can be implemented.

[0056] Example

[0057] Representative examples of this embodiment are shown below, but this embodiment is not limited to these examples.

[0058] The average particle size of the ferrite particle powder used in the present example was measured using "Sub-Sieve Sizer Model 95" (manufactured by Fisher Scientific).

[0059] The BET specific surface area of ​​the ferrite particle powder used in the present example was measured using a "fully automatic specific surface area meter Macsorb model-1201" (manufactured by MountTech Corporation).

[0060] The molding density of the molded body molded using the bonded magnet resin composition is determined as follows. First, the bonded magnet resin composition is molten in a metal mold of 25 mm Φ and 10.5 mm in height to form a core. The core is measured using an "electronic densimeter EW-120SG" (manufactured by Yasuda Seiki Co., Ltd.) to determine the molding density of the molded body.

[0061] The melt flow rate (MFR) of the resin composition for bonded magnets is determined as follows according to JIS K7210. For resins having a PA10 skeleton, melting is carried out at 270°C and 300°C. For resin compositions for bonded magnets using PA12 resin or PA6 resin, melting is carried out at 270°C. For resin compositions for bonded magnets using PPS resin, melting is carried out at 330°C. By measuring these under a load of 10 kg, the melt flow rate (MFR) of the resin composition for bonded magnets is determined.

[0062] The magnetic properties (residual magnetic flux density Br, coercive force iHc, coercive force bHc, and maximum energy product (BH)max) of the bonded magnet resin composition were determined as follows.

[0063] First, the resin composition for bonded magnets was molten in a metal mold of 25 mm Φ and 10.5 mm in height using an injection molding machine J55AD manufactured by Nippon Steel Works, Ltd., and oriented in a magnetic field at 716.2 kA / m (9 kOe) and molded. Then, the molded body was measured in a magnetic field of 1114.1 kA / m (14 kOe) using a "DC magnetization characteristic automatic recording device 3257" (manufactured by Yokogawa Hokushin Electric Co., Ltd.), thereby obtaining the above-mentioned magnetic properties.

[0064] The bending strength and IZOD impact strength of the molded body molded using the resin composition for bonded magnets were obtained as follows according to ASTM D790 and D256 standards. The test piece molded body was obtained using the injection molding machine J55AD of Japan Steel Works, Ltd. Then, the test piece molded body was measured using the computer measurement and control precision universal testing machine AG-1 manufactured by Shimadzu Corporation and NO.158 manufactured by Yasuda Seiki Seisakusho Co., Ltd., thereby obtaining the bending strength and IZOD impact strength.

[0065] The water absorption of the molded body molded using the resin composition for bonded magnets is calculated as follows. First, a test piece molded body is obtained using an injection molding machine J55AD of The Japan Steel Works, Ltd. Then, the test piece molded body is exposed for 100 hours in an environment of 85°C / 90%RH using a constant temperature and humidity testing apparatus LHL-113 of ESPEC Corporation. Next, the weight of the molded body before and after exposure is measured. Using these weights, the water absorption of the molded body is calculated according to the following formula.

[0066] ((weight after exposure - weight before exposure) / weight before exposure)×100[wt%]

[0067] The load deflection temperature of the molded body molded using the resin composition for bonded magnets is determined as follows according to the ASTM D648 standard. Using the injection molding machine J55AD of Japan Steel Works, Ltd., a test piece molded body with a total length of 127 mm, a total width of 13 mm, and a thickness of 3.2 mm is obtained. Then, the load deflection temperature of the molded body is determined by measuring the test piece molded body using the HDT test device 3M-2V of Toyo Seiki Seisaku-sho, Ltd. (test direction: along the edge, test stress: 1.82 MPA).

[0068] Example 1

[0069] In 75.00 parts by weight of ferrite particle powder (average particle size: 1.20 μm, BET value: 1.75 μm) 2 / g, coercive force 226kA / m (2850Oe), saturation magnetization 822Am 2 / kg (72emu / g)) was added with 0.50 parts by weight of an aminoalkyl silane coupling agent, and heated and mixed at 100°C until uniform. Thus, a surface-treated ferrite particle powder was obtained. The surface-treated ferrite particle powder, 24.29 parts by weight of PA410 resin, and 0.21 parts by weight of an antioxidant were fully mixed using a Henschel mixer. It should be noted that the melting point of PA410 resin is 250°C.

[0070] The obtained mixture was quantitatively supplied to a biaxial kneading machine and kneaded at 270° C. The kneaded product was then taken out in a strand shape and cut into pellets of 2 mmΦ×3 mm in size. Thus, a resin composition for a bonded magnet was obtained.

[0071] The composition of the obtained bonded magnet resin composition is shown in Table 1. Table 2 also shows the molded density, MFR, and magnetic properties of the bonded magnet resin composition of each example.

[0072] The flexural strength, IZOD impact strength, load deflection temperature, and water absorption of the test piece molded body obtained by injection molding the bonded magnet resin composition of each example were measured. The results are shown in Table 3.

[0073]

[0074]

[0075]

[0076] Embodiments 2 to 6

[0077] Bonded magnet resin compositions were prepared in the same manner as in Example 1 except that the composition of the ferrite particle powder, the silane coupling agent, the PA410 resin, the glass fiber and the antioxidant was variously changed as shown in Table 1.

[0078] Embodiments 7 to 11

[0079] The resin composition for bonded magnets was prepared in the same manner as in Example 1 except that the binder resin was changed to PA610 resin and the ferrite particle powder, silane coupling agent, PA610 resin, glass fiber and antioxidant were variously changed as described in Table 1. It should be noted that the melting point of PA610 resin is 225°C.

[0080] Comparative Examples 1 and 2

[0081] The resin composition for bonded magnets was prepared in the same manner as in Example 1 except that the binder resin was changed to PA12 resin and the ferrite particle powder, silane coupling agent, PA12 resin, glass fiber and antioxidant were variously changed as described in Table 4. It should be noted that the melting point of PA12 resin is 176°C.

[0082] Table 5 shows the mold density, MFR, and magnetic properties of the bonded magnet resin composition of the comparative example obtained.

[0083] Table 6 shows the results of measuring the flexural strength, IZOD impact strength, load deflection temperature, and water absorption of the test piece molded body obtained by injection molding the bonded magnet resin composition of the comparative example.

[0084] Comparative Examples 3 and 4

[0085] The resin composition for bonded magnets was prepared in the same manner as in Example 1 except that the binder resin was changed to PA6 resin and the blending of ferrite particle powder, silane coupling agent, PA6 resin and antioxidant was changed as described in Table 4. It should be noted that the melting point of PA6 resin is 225°C.

[0086] Comparative Examples 5 and 6

[0087] The resin composition for bonded magnets was prepared in the same manner as in Example 1 except that the binder resin was changed to PPS resin and the blending of ferrite particle powder, silane coupling agent, PPS resin and antioxidant was changed as described in Table 4. The melting point of PPS resin is 280°C.

[0088] [Table 4]

[0089]

[0090] [Table 5]

[0091]

[0092] [Table 6]

[0093] project unit Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Comparative Example 5 Comparative Example 6 Bending Strength MPa 130 128 191 188 104 106 IZOD impact strength (unnotched) <![CDATA[kJ / m 2 ]]> NB 21.6 NB 20.7 8.4 7.6 Deflection Temperature under Load ℃ 135 136 163 176 210 219 Water absorption wt% 0.30 0.20 1.30 1.10 0.05 0.04

[0094] ※NB: No cracks

[0095] It was confirmed that the bonded magnet resin composition of this embodiment has excellent properties related to load deflection temperature compared with the bonded magnet resin composition of Comparative Examples 1 and 2 containing PA12 resin. In addition, it was confirmed that the bonded magnet resin composition of the embodiment has excellent properties related to water absorption compared with the bonded magnet resin composition of Comparative Examples 3 and 4 containing PA6 resin. It should be noted that the bonded magnet resin composition of the embodiment has excellent properties related to bending strength and IZOD impact strength compared with the bonded magnet resin composition of Comparative Examples 5 and 6 containing PPS resin.

[0096] Industrial Applicability

[0097] Therefore, if the bonded magnet resin composition of this embodiment is used, a molded body having reduced water absorption while maintaining high magnetic properties, physical properties and load deflection temperature can be obtained. Therefore, the bonded magnet resin composition of this embodiment is suitable as a bonded magnet material.

Claims

1. A resin composition for bonded magnets, comprising at least magnetic powder and a binder resin, Containing 70% by weight or more of the magnetic powder, and The binder resin contains 5 to 30% by weight of a resin having a PA10 skeleton.

2. The bonded magnet resin composition according to claim 1, wherein The melting point of the resin having a PA10 skeleton is above 200°C.

3. The bonded magnet resin composition according to claim 1 or 2, wherein Contains 10% by weight or less of an inorganic reinforcing material. 4 . A bonded magnet molded body formed using the bonded magnet resin composition according to claim 1 .

Citation Information

Patent Citations

  • Plastic magnetic composition

    JP1992044304A

  • Bond magnet composition and molded product made thereof

    JP2005072240A

  • Resin composition for bonded magnet, and bonded magnet using the same

    JP2015076572A